2015
DOI: 10.1007/s12098-014-1659-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth Patterns of HIV Infected Indian Children in Response to ART: A Clinic Based Cohort Study

Abstract: The prevalence of stunting and underweight was high at ART initiation. Sustained catch-up growth was seen with ART. The study highlights the benefit of early ART in achieving normal growth in CLHIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…No statistical differences were observed in initial body weight, assessed from PD 8 to PD 10, results which are consistent with those previously reported in male Sprague-Dawley rats stereotaxically injected with Tat and/or gp120, HIV-1 viral proteins, on PD 1 (Fitting et al 2008) and in HIV-1 infected children (Guillen et al 2007; Parachure et al 2015). HIV-1 Tg animals exhibited later eye opening, indicating an early selective alteration in somatic growth.…”
Section: Discussionsupporting
confidence: 91%
“…No statistical differences were observed in initial body weight, assessed from PD 8 to PD 10, results which are consistent with those previously reported in male Sprague-Dawley rats stereotaxically injected with Tat and/or gp120, HIV-1 viral proteins, on PD 1 (Fitting et al 2008) and in HIV-1 infected children (Guillen et al 2007; Parachure et al 2015). HIV-1 Tg animals exhibited later eye opening, indicating an early selective alteration in somatic growth.…”
Section: Discussionsupporting
confidence: 91%
“…This resulted in the BMI rapidly increasing to above the zero Z-score during the first year of treatment, with this effect more pronounced in infants. This ART-related growth improvement is comparable to descriptions from other ART follow-up studies from India and Southern Africa [15,22,24,26]. At the end of the 5-year follow-up period, stunting was the most important growth deficit observed in 20.2% of children, which is higher than South African malnutrition data in the age group 5-10 years in the year 2005 (13.9%) [32].…”
Section: Discussionsupporting
confidence: 82%
“…Age at ART initiation impacted on growth improvement: Children older than 3 years experienced a lower weight and height increase than younger children, and this resulted in better BMI outcome in infants, while height outcomes did not differ across age groups. Previous studies consistently describe improved weight outcomes for younger children [16,18,21,22,24,26,[35][36][37][38], possibly related to less severe gastrointestinal impairment and shorter duration of chronic immune activation [39,40]. Reports on the impact of age on height differ between studies, with improved height outcomes with younger age in some studies [23,24,26,35], while others reported no difference [36] or worse height outcomes for younger children [20,22].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations